Gambaran tingkat pengetahuan dan kesadaran penggunaan kacamata pada lansia - Muzakki, Muhammad Alfian; Putra, Meirizal Ari (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Older adults are defined as individuals aged 60 years and above. According to the World Health Organization (WHO), aging is classified into several stages, including older adults (60–74 years), old-old (75–90 years), and very old (>90 years), with individuals aged 45–59 years categorized as the pre-elderly group. Aging is commonly accompanied by a decline in visual function due to physiological changes in the eye, including reduced accommodative ability, decreased reading capacity, and impaired color vision. Purpose: To describe the level of knowledge and awareness regarding the use of eyeglasses as visual aids among older adults. Method: Descriptive quantitative research using a cross-sectional design involving 49 respondents. Results: The majority of respondents were female (75.5%, n = 37). Most respondents were in the age group of 51–60 years (42.9%, n = 21). The predominant level of knowledge was moderate, reported by 63.3% (n = 31) of respondents, followed by good knowledge at 16.3% (n = 8), while 20.4% (n = 10) had poor knowledge. In contrast, awareness regarding the use of eyeglasses was predominantly low, with 83.7% (n = 41) of respondents categorized as not aware of the importance of using eyeglasses, whereas only 16.3% (n = 8) demonstrated adequate awareness.. Conclusion: The level of knowledge is sufficient (63.3%) that using glasses is important but awareness of using glasses is low at 83.7%. Keywords: Eyeglasses Awareness; Knowledge. Pendahuluan: Lansia adalah usia diatas rata-rata 60 tahun keatas, menurut WHO klasifikasi usai lanjut yaitu terbagi menjadi beberapa kategori seperti lansia (60-74 tahun), lansia tua (75-90 tahun), dan sangat tua (>90 tahun) dengan usia pertengahan (45-59 tahun) sebagai kelompok pra-lansia. Usia lanjut menyebabkan penurunan pengelihatan sebab respons- respons perseptual terhadap lingkungan berhubungan dengan rasa aman. Penurunan penglihatan (low vision) dan fungsi penglihatan yang dianggap normal seiring proses penuaan termasuk fisiologi penglihatan yang berkurang, penurunan kemampuan mata untuk membaca dan penglihatan warna. Tujuan: Untuk mengetahui gambaran tingkat pengetahuan dan kesadaran dalam penggunaan kacamata sebagai alat bantu pengelihatan pada lansia. Metode: Peniltian kuantitatif deskriptif dengan menggunakan desain cross sectional yang melibatkan 49 responden. Hasil: Jenis kelamin di dominasi perempuan sebanyak 75.5% (37) Responden dengan usia responden dominan usia 51-60 tahun sebanyak 6.1% (21) Responden. Tingkat pengetahuan tertinggi yaitu pengetahuan cukup sebanyak 63.3% (31) Responden, lalu pengetahuan baik sebanyak 16.3% (8) Responden sedangkan pengetahuan kurang sebanyak 20.4% (10) Responden. Tingkat kesadaran dalam penggunaan kacamata tertinggi tidak sadar sebanyak 83.7% (41) Responden dan tingkat kesadaran pentingnya penggunaan kacamata yaitu sebanyak 16.3% (8) Responden. Simpulan: Tingkat pengetahuan cukup (63.3%) bahwa penggunaan kacamata itu penting namun rendah dalam sadar untuk menggunakan kacamata sebanyak 83.7%. Kata Kunci: Kacamata; Kesadaran; Pengetahuan.